2011
DOI: 10.2147/ijn.s24353
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of dentistry: nanotechnology

Abstract: Abstract:The human body comprises molecules; hence, the availability of molecular nanotechnology will permit dramatic progress to address medical problems and will use molecular knowledge to maintain and improve human health at the molecular scale. Nanomedicine could develop devices that are able to work inside the human body in order to identify the early presence of a disease, and to identify and quantify toxic molecules and tumor cells, for example. Nanodentistry will make possible the maintenance of compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 12 publications
0
56
0
1
Order By: Relevance
“…Nanocomposite films can be used to deliver antimicrobials such as tetracycline and alendronate to periodontal pocket fluids via guided tissue regeneration membranes, reducing alkaline phosphatase activity and bone formation 48 . Some products have been developed to treat dentin hypersensitivity, including dentifrices with nanocrystals that can selectively occlude tubules, offering patients a permanent cure 49 . Another study demonstrated that a desensitiser product based on nanostructured bioactive glass reduces tubular fluid flow and, probably, dentinal hypersensitivity 50 .…”
Section: Nanotechnology and Dental Applicationsmentioning
confidence: 99%
“…Nanocomposite films can be used to deliver antimicrobials such as tetracycline and alendronate to periodontal pocket fluids via guided tissue regeneration membranes, reducing alkaline phosphatase activity and bone formation 48 . Some products have been developed to treat dentin hypersensitivity, including dentifrices with nanocrystals that can selectively occlude tubules, offering patients a permanent cure 49 . Another study demonstrated that a desensitiser product based on nanostructured bioactive glass reduces tubular fluid flow and, probably, dentinal hypersensitivity 50 .…”
Section: Nanotechnology and Dental Applicationsmentioning
confidence: 99%
“…This approach is still not viable as many of the devices used to operate at nano level are still being developed. 5,6,7 …”
Section: Top -Down Techniquementioning
confidence: 99%
“…The self-replication of molecule has to be carefully controlled so it does not go out of hand. 5,6,7 …”
Section: Bottom -Up Approachmentioning
confidence: 99%
“…This feather of nano-particles provides a larger surface space per unit mass than those which are not in nano size [1].…”
Section: Introductionmentioning
confidence: 99%